Type 1 Brugada Pattern Unmasked During the Recovery Phase of Treadmill Test - Dagostin de Carvalho, Guilherme; Armaganijan, Luciana Vidal; Giovanini, Eduardo; Alves, César Henrique Morais; Aguiar, Vinícius Motta Machado de; Ribeiro, Silvio Zampieri; Gasparotto Júnior, Luadir; Demarchi, Amanda Vanessa; Montesi, Marcos Vinícius de Oliveira; Medeiros, Paulo de Tarso Jorge (JOURNAL OF CARDIAC ARRHYTHMIAS, 2022)
We described a case of a 39-year-old asymptomatic patient presenting a coved type 1 Brugada pattern during the recovery phase of treadmill testing. Electrophysiological study resulted in induced polymorphic ventricular tachycardia and implantable cardioverter defibrillator was indicated.